Familial Hypocalciuric Hypercalcaemia (FHH): A Case Report - Kulasegaran, Tivya; Kumar, Pranav (International Journal of Innovative Research in Medical Science, 2018)
Familial hypocalciuric hypercalcaemia (FHH) is a rare genetic autosomal dominant disorder, with 3 variants described. An inactivating mutation in the calcium sensor receptor (CASR) gene causes the subtype 1, which represents 65% of the cases. Inactivation of Ca-sensing receptors (CaSR) can also lead to hypercalcemia associated with increased parathyroid hormone (PTH) secretion.[1] It is characterised by causes mild asymptomatic hypercalcemia[2] and hypocalciuria with normal or elevated PTH. FHH is generally asymptomatic and treatment is not needed. Differential diagnosis with primary hyperparathyroidism (PHPT) is crucial and based on calcium-creatinine clearance ratio (CCCR), which, when under 0.02 points to the diagnosis of FHH.[3] Genetic test is necessary for confirmation.[4]